Impact of Built Environment on the Process of Psychological Treatment of Children and Youth - Agata Gawlak; Ewa Banaś (Buildings)
According to official surveys, the number of adolescents with mental health problems in Poland is increasing, which is also typical of other European countries. At the same time, programmes are being introduced to secure infrastructure and adequate therapeutic space by expanding or creating new, architecturally friendly centres. The comfort of the stay created by appropriate spatial conditions must be developed with the participation of the users (patients, staff and visitors). A qualitative study was carried out among staff, based on the structured interview method. The aim of the study was to diagnose the elements of architectural space that support health. It was hypothesised that the architecture of health care facilities could promote mental health. Using advances in environmental psychology, evidence-based design, and elements such as architectural form, spatial-functional layout and the surrounding environment were considered. The results of the study identified features of a user-friendly environment, creating a set of recommendations based on the research-by-design method. Consequently, the recommendations were implemented into the conceptual design. Their validity was proven using the example of the design of a health centre for young people in Klawa, Poland.